Piston-cylinder for thermodynamic cyclic process - Soh, Kewei. (2009)
The Piston-Cylinder simulation enables users to mimic laboratory Piston-Cylinder operations and would play an important role for undergraduates to grow their intuition on molecular behavior related to real life situation. This research project would focus on the simulation methods used in the construction of the molecular simulation apparatus of the Piston-Cylinder base on the fixation of NVT (number of molecules, volume, and temperature) and NPT (number of molecules, pressure, and temperature). The research would look into the physic and working mechanism behind the fixation of NPT (number of molecules, pressure, and temperature) and the algorithm in creating a piston head which would fluctuate via force balance by collision of molecules. The project would compare and discuss in details the equation of motion, thermodynamic properties and algorithm behind the NVT (Stationary Piston head) and the NPT model (fluctuating Piston head).